Operational performance of the wheeled tool-carriers for plowing and ridging - Lal, Harbans; Nunes, Péricles F. (Pesquisa Agropecuaria Brasileira, 2014)
The operational performance of three types of wheeled tool-carrier, Multicultor CPATSA, Multicultor CPATSA II and Policultor PONTAL has been evaluated for plowing and ridging in Bebedouro experiment station of Centre of Agricultural Research for Semi-Arid Tropics/Brazilian Enterprise of Agricultural Research (CPATSA/EMBRAPA) Petrolina in Pernambuco State, Brazil. The speed of operation, turning time at each end, and actual field capacity have been quantified using same pair of animal and operator for each tool frame and operation. The field capacity varied from 436 m2/h to 742 m2/h for plowing and from 2,664 to 3,428 m2/h for ridging with no effect of tool frame type. The overall average for speed of operation and turning time was observed to 0.926 m/s and 25 second respectively, with no significant difference between two operations (plowing and ridging), type of tool frame and various periods during the working day. The estimated field capacity values using the overall average of speed of operation and turning time differed from those values observed during experimentation in the range of + 15.2% for plowing and - 15,67% for ridging.